Evaluation Of Waiting Time For Pediatric Patients At HKBP Balige General Hospital - Faisal Yusuf; Ully Widya Rochmatil Ulla; Oloan Paradongan Tambunan (International Journal of Health Engineering and Technology, 2023)
According to the Decree of the Minister of Health of the Republic of Indonesia Number 129 of 2008 concerning Minimum Hospital Service Standards that for mixed prescriptions is ≤ 60, and for non-concocted prescriptions is ≤ 30. This study was conducted to determine the average waiting time for mixed and non-concocted prescription services. for pediatric patients at HKBP Balige General Hospital with Minimum Service Standards of the Indonesian Ministry of Health. This research is a descriptive study using the observational method of concoction prescriptions and non-concoctions prescriptions for outpatients at the Pharmacy Installation of RSU HKBP Balige for the period of July 2022. The average result of waiting time for the fastest concoction prescription is 41 minutes and the longest is 60 minutes, while the average result waiting for the fastest non-concoction recipe is 22 minutes and the longest is 36 minutes. The waiting time for mixed and non-concoction prescription services for pediatric patients at the Pharmacy Installation of HKBP Balige General Hospital has met the specified requirements. For future researchers, this can be supplemented by the level of patient satisfaction with the quality of drug prescription services based on waiting time.